Metamorfosis y comportamiento reproductivo de Caligo eurilochus livius Staudinger, lepidoptera; nymphalidae en el Cirna, Loreto-Perú, 2024 - Figueroa del Aguila de Vásquez, María Elena (2024)
The aim of the thesis was to evaluate the metamorphosis and reproductive behaviour of Caligo eurilocus livius at CIRNA, Loreto-Peru, during February-August 2024. The non- experimental descriptive research included 30 eggs to analyse the biological cycle, controlling the periods of larval, prepupal, pupal and adult stages, and all developmental stages were measured with a vernier in a stereoscope. Adults were marked and released in the butterfly house to observe their reproductive behaviour. Results indicate that the egg is white, almost spherical, 1.9 mm in diameter, with parallel striations. The larvae go through 5 instars, changing from white to green and then to brown. The pupa is dark brown, with a thoracic hump, black spines and rigid texture. The adult butterfly has light brown ventral wings with ocelli and dark and dull blue dorsal wings, with an average life span of 46 ± 3.3 days. The average lengths of the immature stages are: first instar 6.1 ± 0.5 days, second 4.9 ± 0.5 days, third 5.6 ± 0.7 days, fourth 6.6 ± 0.8 days and fifth 12.9 ± 1.2 days, reaching 70.8 ± 1.2 mm in length and cephalic capsule of 8.2 ± 1.3 mm. The prepupa lasts 2.9 ± 0.3 days and the pupa 13.3 ± 0.5 days, with an average size of 45.2 ± 1.3 mm. The butterfly is crepuscular, ovipositing on Heliconia latispatha (95%). The sex ratio is 1:1.3 (12 females and 16 males), and females lay an average of 405 eggs.